Analisis Perbandingan Cost-Effectiveness Penggunaan Obat Antihipertensi Generik dan Merek di Apotek Gembleb Farma Trenggalek Berbasis Outcome Pasien - Saristiana, Yuneka; Prasetyawan, Fendy; Probosiwi, Neni (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah, 2025)
Hypertension is a chronic disease that requires long-term therapy with continuous use of drugs. This study aims to analyze the cost-effectiveness comparison between generic and branded antihypertensive drugs in patients at Gembleb Farma Trenggalek Pharmacy. The study was conducted by comparing demographic characteristics, therapy costs, clinical outcomes in the form of blood pressure reduction, and patient compliance levels. The results showed that the basic characteristics of patients in both groups were relatively equivalent so that comparisons could be made objectively. In terms of cost, branded drugs were on average almost three times more expensive than generic drugs (IDR 163,000 vs IDR 67,000 per month), while clinical outcomes showed no significant difference. The level of patient compliance in both groups was also relatively similar. Pharmacoeconomic analysis showed that generic drugs had a lower cost-effectiveness ratio, with the incremental cost-effectiveness ratio indicating the additional cost of branded drugs was not worth the minimal additional clinical benefit.